Tipe Kepemimpinan Kepala Sekolah - Sukatin; Muammar Qadafi; Inda Salsabila; Sindy Septia Bella; Feni Angaria; Riski Firmansyah (Medan Resource Center, 2022)
A leader is essentially a person who has the ability to influence the behavior of others in his work by using power. It is in his activities that the leader has the power to mobilize and influence his subordinates in connection with the tasks to be carried out. The types of principal leadership are generally personal leadership types, Non-personal leadership types, authoritarian leadership types, democratic leadership types, paternalist leadership types, leadership types by talent. The duties of the leader in his leadership include; diving into the needs of the citizens of the school he leads, from which desires can be learned realistic and truly achievable wills, convincing his subordinates of what is their will, which is realistic and which is actually a delusion. A professional leader is a leader who understands his duties and obligations, and can establish a good cooperative relationship with subordinates, so as to create a working atmosphere that makes subordinates feel safe, peaceful, and have a freedom in developing their ideas in order to achieve the common goals that have been set.